The effect of bone marrow graft composition on pediatric bone marrow transplantation outcomes. (29th August 2018) - Fabrizio, Vanessa; Wahlquist, Amy; Hill, Elise; Williams, Elizabeth; Kramer, Cindy; Jaroscak, Jennifer; Duong, Angie; Garrett‐Mayer, Elizabeth; Hudspeth, Michelle
Abstract: Hematopoietic stem cell graft cellular composition has been generally accepted to impact outcomes. Recent studies question this hypothesis. We conducted a single‐center retrospective study of sixty‐one pediatric BMT recipients for malignant (68%) and nonmalignant diseases (32%) examining effects of graft composition on engraftment, acute GVHD, chronic GVHD, and survival at day 100 and 1 year. Grafts contained a median of 3.63 x  0 8 TNC/kg (range: 0.031‐10.31 x 10 8 TNC/kg) and 4.09 x 10 6 CD34 + /kg (range: 0.76‐24.15 x 10 6 CD34 + /kg) with median neutrophil and platelet engraftment times of 17 and 29 days, respectively. A univariate analysis showed a trend for increasing TNC and increasing time to neutrophil engraftment HR: 0.875; CI: 0.075‐1.001). Increasing CD34 + counts shortened time to platelet engraftment (HR: 1.085; CI: 1.015‐1.161). No significant relationship was found between TNC, CD34 +, or CD3 + and acute or chronic GVHD. TNC or CD34 + did not affect day 100, 1‐year survival, or 2‐year survival. Increasing CD3 + counts demonstrated a negative trend on day 100 survival (HR: 1.108; CI: 1.001‐1.036) but not 1‐year survival or 2‐year survival. These results add additional data questioning the effect of graft composition on outcomes in pediatric BMT patients with important ramifications for the management of donors.